Synthesis method and application method of co-doped perovskite nanocrystal
By introducing Zn2+ and Mn2+ dopants into CsPbX3 nanocrystals, combined with ultrasonic technology to synthesize co-doped perovskite nanocrystals at room temperature, the stability and optical characteristics regulation of nanocrystals are solved, and the specific detection of Cu2+ is achieved , expanding its application potential in the fields of photoelectronics and photovoltaics.
Patent Information
- Application Number
- CN202411504121.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
AI Technical Summary
Existing lead-based halide perovskite nanocrystals have crystal structure defects and fragility during the synthesis process, limiting their application in the fields of photoelectronics and photovoltaics, and the toxicity of lead poses a challenge to commercial feasibility.
Using a dual replacement strategy, the co-doped perovskite nanocrystals were synthesized at room temperature by introducing Zn2+ and Mn2+ as dopants in CsPbX3 nanocrystals, combined with ultrasonic technology, to improve its stability and allow tuning control of optical properties, and successfully Applied to specific detection of Cu2+.
The stability and luminous performance of CsPbX3 nanocrystals were significantly improved, the optimal control of optical properties was achieved, and the successful detection of Cu2+ by co-doped perovskite nanocrystals was demonstrated, demonstrating its potential in the fields of photoelectronics and photovoltaics.
Smart Images

Figure CN119242303A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent materials and relates to a synthesis method and application of co-doped perovskite nanocrystals. Background Art
[0002] Lead-based halide perovskite colloidal nanocrystals (PNCs) have attracted extensive attention due to their remarkable photophysical and electronic properties. These properties include high color purity, wide color gamut, tunable band gap, high photoluminescence quantum yield, simple synthesis method, and tunable luminescence that can be adjusted by changing the halogen composition. Lead-based halide PNCs are mainly divided into two categories: organic-inorganic hybrid halide PNCs (APbX3, where A is methylammonium or formamidine; X represents Cl, Br, or I) and all inorganic cesium lead halide PNCs (CsPbX3). CsPbX3 (where X = Cl, Br, I) PNCs represent the classic category of all inorganic halide perovskite nanomaterials, and their remarkable features make them promising candidates for light-emitting diodes, laser technology, photodetectors, photovoltaic cells, and fluorescence sensing applications.
[0003] CsPbX3 PNCs are mainly synthesized by two main techniques: high-temperature hot injection (HI) and room-temperature ligand-assisted reprecipitation (LARP) method. The HI method requires high temperature and inert atmosphere to achieve optimal results, which makes it relatively complex and energy-consuming. In contrast, the LARP method has significant advantages and can synthesize PNCs at room temperature, simplifying the process and reducing energy costs. In the LARP method, the precursor material is first dissolved in a polar solvent such as N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). It is then mixed with a non-polar solvent to promote the formation of nanocrystals. Although both methods can produce a large amount of PNCs, they usually result in defective and fragile crystal structures, which may limit their applications. Compared with these techniques, the ultrasonication technique has significant advantages because it eliminates the need for pretreatment or degassing of the precursors, allowing synthesis in an open environment. As a representative bottom-up method, this method facilitates the nucleation and growth of high-quality PNCs while minimizing time and energy consumption. Typically, the reactants used for the sonication synthesis of all inorganic PNCs include capping ligands, inorganic salts (such as cesium and lead halides), and an appropriate solvent. The simplicity and efficiency of this method make it an attractive option for researchers aiming to develop high-quality PNCs with reduced environmental impact. Further optimization of sonication parameters could improve the properties of the synthesized nanocrystals, potentially expanding their applications in optoelectronics and photovoltaics.
[0004] The toxicity of lead in CsPbX3 (where X = Cl, Br, I) PNCs poses a considerable challenge to their commercial viability. Although completely eliminating lead to make lead-free PNCs is not a suitable option, replacing Pb with multivalent metal ions is a promising approach. 2+ It has been proved to be an effective strategy. By incorporating a small amount of alternative metal ions at the B site, the excellent optoelectronic properties of natural nanocrystals can be significantly enhanced or new functions can be introduced. Divalent metal dopants, such as Zn 2+ , Mn 2+ and Ni 2+ , have been shown to enhance the radiative recombination rate. This improvement has been attributed to specific hybridization effects with the host lattice or nonspecific effects caused by interruptions in the lattice periodicity. Among these metals, Zn 2+ and Mn 2+ It is particularly suitable as a dopant for PNC. 2+ (119 pm) compared to their smaller ionic radii (Zn 2+ 74pm, Mn 2+ 80pm) and low toxicity, making it an ideal substitute. Summary of the invention
[0005] The present invention provides a method for synthesizing and applying co-doped perovskite nanocrystals, which effectively improves the stability of CsPbX3 (where X=Cl, Br, I) nanocrystals through this double substitution strategy, while allowing optimal control of the tuning of optical properties, and is successfully applied to Cu 2+ Specific detection.
[0006] A method for synthesizing co-doped perovskite nanocrystals comprises the following steps:
[0007] Step (1) Preparation of precursor solution: CsCl, PbCl2, oleic acid (OA) and oleylamine (OLAM) were dissolved in dimethyl sulfoxide (DMSO) in a serum bottle to obtain precursor solution A; MnCl2·4H2O was dissolved in DMF to form precursor solution B, and ZnCl2 was dissolved in DMF to produce precursor solution C; the above precursor solutions were treated by tip sonication at room temperature for 30 minutes until they were completely dissolved;
[0008] Step (2) Synthesis of co-doped perovskite nanocrystals: Precursor solution B, precursor solution C and precursor solution A are mixed and added dropwise into toluene (TOL) under vigorous stirring;
[0009] Step (3) centrifuging the reaction mixture at 10,000 rpm for 15 minutes to obtain co-doped perovskite nanocrystals, and discarding the supernatant to eliminate unreacted precursors; redispersing the precipitate in TOL and centrifuging it at 8,000 rpm for 10 minutes twice; and then redissolving the final precipitate in TOL as the final nanocrystal product.
[0010] A method for applying co-doped perovskite nanocrystals comprises the following steps:
[0011] Step 1: Preparation of ionic solution: 0.1 mmol chloride was mixed with 1 mL water in a centrifuge tube; then, 0.25 mmol sodium oleate was dissolved in a mixture of water and ethanol in a volume ratio of 1:1 and added to the chloride solution, copper oleate was separated by centrifugation and vacuum dried at 75°C for 24 hours; then dissolved in toluene in a 10 mL volumetric flask to prepare a 1 mmol / L metal solution;
[0012] Step 2: Detection of metal ions: Take 1 mL 10 -8 M co-doped perovskite nanocrystals with 1mL 10 -8 After mixing and shaking for one minute to ensure complete interaction with the metal ions, the mixture was analyzed using a fluorescence spectrophotometer.
[0013] The present invention selects MnCl2 and ZnCl2, introduces Zn 2+ and Mn 2+ This double substitution strategy effectively improves the stability of CsPbX3 (where X = Cl, Br, I) nanocrystals while allowing optimal control over the tuning of optical properties and is successfully applied to Cu 2+ Specific detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 HR-TEM images of the co-doped perovskite nanocrystals of the present invention at different lattice spacings.
[0015] Figure 2 It is a schematic diagram of the ratio of the co-doped perovskite nanocrystals of the present invention at different particle sizes.
[0016] Figure 3 It is a schematic diagram of TRPL decay analysis of co-doped perovskite nanocrystals of the present invention.
[0017] Figure 4 This is a schematic diagram of the fluorescent probe test results of co-doped perovskite nanocrystals prepared with different metal ions.
[0018] Figure 5The PL intensity of the co-doped perovskite nanocrystals of the present invention is 2+ Schematic diagram of the concentration dependence. DETAILED DESCRIPTION
[0019] A method for synthesizing co-doped perovskite nanocrystals comprises the following steps:
[0020] Step (1) Preparation of precursor solution: CsCl, PbCl2, OA and OLAM were dissolved in DMSO in a serum bottle to obtain precursor solution A; MnCl2·4H2O was dissolved in DMF to form precursor solution B, and ZnCl2 was dissolved in DMF to produce precursor solution C; the above precursor solutions were treated by tip sonication at room temperature for 30 minutes until they were completely dissolved;
[0021] Step (2) Synthesis: Precursor solution B, precursor solution C and precursor solution A are mixed and added dropwise to TOL under vigorous stirring;
[0022] Step (3) centrifuging the reaction mixture at 10,000 rpm for 15 minutes to obtain co-doped perovskite nanocrystals, and discarding the supernatant to eliminate unreacted precursors; redispersing the precipitate in TOL and centrifuging it at 8,000 rpm for 10 minutes twice; and then redissolving the final precipitate in TOL as the final nanocrystal product.
[0023] Preferably, the method for synthesizing co-doped perovskite nanocrystals of the present invention comprises the following steps:
[0024] Step (1) Preparation of precursor solution: 0.4 mmol CsCl, 0.4 mmol PbCl2, 1.0 mL OA and 0.5 mL OLAM were dissolved in 10 mL DMSO in a 20 mL serum bottle to obtain precursor solution A; 2 mmol MnCl2·4H2O was dissolved in 2 mL DMF to form precursor solution B, and 2 mmol ZnCl2 was dissolved in 2 mL DMF to produce precursor solution C; the above precursor solutions were treated by tip sonication at room temperature for 30 minutes until they were completely dissolved;
[0025] Step (2) Synthesis: Precursor solution B and precursor solution C were mixed with 1 mL of precursor solution A and added dropwise to 10 mL of TOL under vigorous stirring;
[0026] Step (3) centrifuging the reaction mixture at 10,000 rpm for 15 minutes to obtain co-doped perovskite nanocrystals, and discarding the supernatant to eliminate unreacted precursors; redispersing the precipitate in 5 mL TOL and centrifuging at 8,000 rpm for 10 minutes twice; and then redissolving the final precipitate in 5 mL TOL as the final nanocrystal product.
[0027] Preferably, in step (2) of the present invention, 1.0 mL of precursor solution B, 1.0 mL of precursor solution C and 1 mL of precursor solution A are mixed.
[0028] Preferably, in step (2) of the present invention, 2.0 mL of precursor solution B, 2.0 mL of precursor solution C and 1 mL of precursor solution A are mixed.
[0029] Preferably, in step (2) of the present invention, 0.5 mL of precursor solution B, 0.8 mL of precursor solution C and 1 mL of precursor solution A are mixed.
[0030] A method for applying co-doped perovskite nanocrystals comprises the following steps:
[0031] Step 1: Preparation of ionic solution: Chloride and water were mixed in a centrifuge tube; subsequently, sodium oleate was dissolved in a mixture of water and ethanol and added to the chloride solution, copper oleate was separated by centrifugation and vacuum dried at 75°C for 24 hours; then dissolved in toluene in a volumetric flask to prepare a 1 mmol / L metal solution;
[0032] Step 2: Detection of metal ions: The co-doped perovskite nanocrystals were mixed with metal ions and shaken for one minute to ensure complete interaction with the metal ions, and then the mixture was analyzed using a fluorescence spectrophotometer.
[0033] Preferably, the application method of the co-doped perovskite nanocrystals of the present invention comprises the following steps:
[0034] Step 1: Preparation of ionic solution: 0.1 mmol chloride was mixed with 1 mL water in a centrifuge tube; then, 0.25 mmol sodium oleate was dissolved in a mixture of water and ethanol in a volume ratio of 1:1 and added to the chloride solution, copper oleate was separated by centrifugation and vacuum dried at 75°C for 24 hours; then dissolved in toluene in a 10 mL volumetric flask to prepare a 1 mmol / L metal solution;
[0035] Step 2: Detection of metal ions: Take 1 mL 10 -8 M co-doped perovskite nanocrystals with 1mL 10 -8 After mixing and shaking for one minute to ensure complete interaction with the metal ions, the mixture was analyzed using a fluorescence spectrophotometer.
[0036] Preferably, the chloride described in step 1 of the present invention is at least one of CuCl2, KCl, NaCl, CaCl2, CoCl2, MgCl2 or AlCl3.
[0037] Example 1
[0038] This embodiment provides a Zn, Mn co-doped 2+ , Zn 2+ ): A method for preparing CsPbCl3 perovskite nanocrystals, the preparation method being as follows:
[0039] (1) Preparation of precursor solutions: 0.4 mmol CsCl, 0.4 mmol PbCl2, 1.0 mL OA, and 0.5 mL OLAM were dissolved in 10 mL DMSO in a 20 mL serum bottle, referred to as precursor solution A. In addition, 2 mmol MnCl2·4H2O was dissolved in 2 mL DMF to form precursor solution B, while 2 mmol ZnCl2 was dissolved in 2 mL DMF to produce precursor solution C. These precursor solutions were treated by tip sonication at room temperature for 30 min until they were completely dissolved.
[0040] (2) Synthesis (Mn 2+ , Zn 2+ ): Synthesis of CsPbCl3-PNCs: 1 mL of precursor solution A was mixed with 1.0 mL of precursor solution B and 1.0 mL of precursor solution C, and added dropwise into 10 mL TOL under vigorous stirring.
[0041] (3) The reaction mixture was centrifuged at 10,000 rpm for 15 minutes to obtain (Mn 2+ , Zn 2+ ): CsPbCl3-PNCs, and discard the supernatant to eliminate unreacted precursors. Subsequently, the precipitate was redispersed in 5 mL TOL and centrifuged at 8000 rpm for 10 minutes twice. The final precipitate was then redissolved in 5 mL TOL as the final nanocrystal product.
[0042] Example 2
[0043] This embodiment provides a (Mn 2+ , Zn 2+ ): Application method of CsPbCl3 perovskite nanocrystals, the application method is as follows:
[0044] (1) Preparation of ionic solution: Taking Cu solution as an example, 0.1 mmol CuCl2 was mixed with 1 mL water in a centrifuge tube. Subsequently, 0.25 mmol sodium oleate was dissolved in a 1:1 (v:v) mixture of water and ethanol and added to the CuCl2 solution. The copper oleate was then separated by centrifugation and vacuum dried at 75 °C for 24 h. Subsequently, it was dissolved in toluene in a 10 mL volumetric flask to prepare a 1 mmol / L Cu solution. Other concentrations of Cu 2+ It was obtained by serial dilution.
[0045] (2)Cu2+ Detection: Take 1mL (10 -8 M) CsPbCl3-PNCs and 1mL (10 -8 M)Cu 2+ After the ions were mixed and shaken for one minute to ensure complete interaction with the quencher (metal ions), the mixture was analyzed using a fluorescence spectrophotometer. The interaction between co-doped (Zn, Mn):CsPbCl3-PNCs and metal ions occurred rapidly and was completed within ten seconds; therefore, shaking for one minute was considered suitable for subsequent fluorescence measurements.
[0046] Example 3
[0047] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the volumes of precursor solution B and precursor solution C are replaced with 2.0 mL and 2.0 mL, respectively.
[0048] The rest of the preparation methods and parameters were the same as those in Example 1.
[0049] Example 4
[0050] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the volumes of precursor solution B and precursor solution C are replaced with 0.5 mL and 0.8 mL, respectively.
[0051] The rest of the preparation methods and parameters were the same as those in Example 1.
[0052] Example 5
[0053] The difference between this embodiment and embodiment 2 is that the CuCl2 in step (1) of this embodiment is replaced by one of KCl, NaCl, CaCl2, CoCl2, MgCl2 or AlCl3.
[0054] The rest of the preparation methods and parameters were the same as those in Example 2.
[0055] In the HR-TEM images, the lattice spacing of CsPbCl3, Mn-doped CsPbCl3-PNC and co-doped (Zn, Mn): CsPbCl3-PNC changes from Reduce to See attached Figure 1 In addition, the average side length of the particles decreased from 20.41 nm to 17.67 nm, see Appendix Figure 2 The gradual decrease in particle size may be due to the Zn 2+ and Mn 2+ Higher doping levels lead to increased lattice shrinkage and enhanced halide ion incorporation, which hinders crystal growth.
[0056] TRPL decay analysis shows that after Zn doping, the lifetime is greatly reduced from 12.1ns to 8.3ns, showing a trend of gradual relaxation. In addition, the characteristic single exponential decay indicates that a single type of luminescence center is responsible for the emission, indicating that Mn 2+ The ions are located in a chemically homogeneous environment within the PNC. After the addition of Zn, the lifetime is shortened from 1.71 to 1.63 ms, which may be due to an increase in non-radiative transitions. These results indicate that Zn doping does not significantly change the structural integrity of the material and largely maintains its optical properties. Figure 3 .
[0057] To evaluate the potential of co-doped (Zn, Mn):CsPbCl3-PNCs as fluorescent probes, various metal ions were tested. + 、Na + , Ca 2+ 、Co 2+ Mg 2+ and Al 3+ Mn 2+ The emission of Cu 2+ Yes. See Appendix Figure 4 It is worth noting that Mn 2+ The PL of Cu 2+ (1×10 -12 M), the quenching effect increases with the concentration to 2×10 -2 Therefore, the co-doped (Zn, Mn):CsPbCl3-PNCs were proved to be an ideal candidate for detecting Cu 2+ The proposed method is a fast and selective PL probe that outperforms CsPbCl3-NCs in terms of specificity. Figure 5 The PL intensity of co-doped (Zn, Mn):CsPbCl3-PNCs is shown to be dependent on the Cu 2+ The concentration dependence of PL intensity shows that the PL intensity decreases steadily with the increase of Cu concentration. -12 Up to 10 -2 MCu 2+ A strong linear correlation was observed within the concentration range, with a correlation coefficient R 2 is 0.9918. This confirms that co-doped (Zn, Mn): CsPbCl3-PNCs can be used as a sensitive detector for Cu 2+ ions as effective fluorescent probes.
Claims
1. A method for synthesizing co-doped perovskite nanocrystals, characterized in that The steps include: Step (1) Preparation of precursor solution: CsCl, PbCl2, oleic acid and oleylamine were dissolved in dimethyl sulfoxide in a serum bottle to obtain precursor solution A; MnCl2·4H2O was dissolved in DMF to form precursor solution B, and ZnCl2 was dissolved in DMF to produce precursor solution C; the above precursor solutions were treated by tip sonication at room temperature for 30 minutes until they were completely dissolved; Step (2) Synthesis of co-doped perovskite nanocrystals: Precursor solution B, precursor solution C and precursor solution A are mixed and added dropwise into toluene under vigorous stirring; Step (3) centrifuging the reaction mixture at 10,000 rpm for 15 minutes to obtain co-doped perovskite nanocrystals, and discarding the supernatant to eliminate unreacted precursors; redispersing the precipitate in toluene and centrifuging it at 8,000 rpm for 10 minutes twice; and then redissolving the final precipitate in toluene as the final nanocrystal product.
2. The method for synthesizing co-doped perovskite nanocrystals according to claim 1, characterized in that The steps include: Step (1) Preparation of precursor solution: 0.4 mmol CsCl, 0.4 mmol PbCl2, 1.0 mL oleic acid and 0.5 mL oleylamine were dissolved in 10 mL dimethyl sulfoxide in a 20 mL serum bottle to obtain precursor solution A; 2 mmol MnCl2·4H2O was dissolved in 2 mL DMF to form precursor solution B, and 2 mmol ZnCl2 was dissolved in 2 mL DMF to produce precursor solution C; the above precursor solutions were treated by tip sonication at room temperature for 30 minutes until they were completely dissolved; Step (2) Synthesis of co-doped perovskite nanocrystals: Precursor solution B and precursor solution C were mixed with 1 mL of precursor solution A, and added dropwise into 10 mL of toluene under vigorous stirring; Step (3) centrifuging the reaction mixture at 10,000 rpm for 15 minutes to obtain co-doped perovskite nanocrystals, and discarding the supernatant to eliminate unreacted precursors; redispersing the precipitate in 5 mL of toluene and centrifuging at 8,000 rpm for 10 minutes twice; and then redissolving the final precipitate in 5 mL of toluene as the final nanocrystal product.
3. The method for synthesizing co-doped perovskite nanocrystals according to claim 1 or 2, characterized in that In step (2), 1.0 mL of precursor solution B, 1.0 mL of precursor solution C and 1 mL of precursor solution A are mixed.
4. The method for synthesizing co-doped perovskite nanocrystals according to claim 1 or 2, characterized in that In step (2), 2.0 mL of precursor solution B, 2.0 mL of precursor solution C and 1 mL of precursor solution A are mixed.
5. The method for synthesizing co-doped perovskite nanocrystals according to claim 1 or 2, characterized in that In step (2), 0.5 mL of precursor solution B, 0.8 mL of precursor solution C and 1 mL of precursor solution A are mixed.
6. A method for applying the co-doped perovskite nanocrystals synthesized according to claim 1, characterized in that The steps include: Step 1: Preparation of ionic solution: Chloride and water were mixed in a centrifuge tube; subsequently, sodium oleate was dissolved in a mixture of water and ethanol and added to the chloride solution, copper oleate was separated by centrifugation and vacuum dried at 75°C for 24 hours; then dissolved in toluene in a volumetric flask to prepare a 1 mmol / L metal solution; Step 2: Detection of metal ions: The co-doped perovskite nanocrystals were mixed with metal ions and shaken for one minute to ensure complete interaction with the metal ions, and then the mixture was analyzed using a fluorescence spectrophotometer.
7. The method for applying co-doped perovskite nanocrystals according to claim 6, characterized in that The steps include: Step 1: Preparation of ionic solution: Mix 0.1 mmol of chloride with 1 mL of water in a centrifuge tube; Subsequently, 0.25 mmol of sodium oleate was dissolved in a mixture of water and ethanol in a volume ratio of 1:1 and added to the chloride solution, and copper oleate was separated by centrifugation and vacuum dried at 75°C for 24 hours; then dissolved in toluene in a 10 mL volumetric flask to prepare a 1 mmol / L metal solution; Step 2: Detection of metal ions: Take 1 mL 10 -8 M co-doped perovskite nanocrystals with 1mL 10 -8 After mixing and shaking for one minute to ensure complete interaction with the metal ions, the mixture was analyzed using a fluorescence spectrophotometer.
8. The method for applying co-doped perovskite nanocrystals according to claim 6 or 7, characterized in that The chloride described in step 1 is at least one of CuCl2, KCl, NaCl, CaCl2, CoCl2, MgCl2 or AlCl3.
